Pengaruh Brand Ambassador Dan Brand Image Terhadap Impulsive Buying Pada Produk Oreo X Blackpink Studi Kasus Pada Mahasiswa Politeknik Negeri Malang - Joy Gabriel Elaine Sambo; Asminah Rachmi (CV. ITTC INDONESIA, 2024)
This research is motivated by the phenomenon of the increasing impulsive buying behavior towards Oreo products, that use a popular brand ambassador, Blackpink. The objective of this study is to determine the influence of brand ambassadors and brand image on impulsive buying among students at the State Polytechnic of Malang. The research employs a quantitative approach using a survey method. The sample comprises 100 students from the State Polytechnic of Malang, and was selected through purposive sampling. Data were collected by online questionnaire and analyzed using SPSS software for data analysis. The findings indicated that the brand ambassador has a positive impact on the impulsive buying of Oreo Blackpink products. Moreover, the brand image also positively influences impulsive buying. Simultaneously, both variables contributed positively to impulsive buying. Based on the findings, it is recommended that Oreo companies continuously enhance the appeal of their brand ambassadors and strengthen their brand image to increase impulsive buying.